A developmental approach to alcohol drinking behaviour in adulthood: a follow-up study from age 8 to age 42. - Pitkänen T; Kokko K; Lyyra AL; Pulkkinen L (Addiction)
AIMS: To study the links of family background, child and adolescent social behaviour, and (mal)adaptation with heavy drinking by age 20 and with the frequency of drinking, binge drinking, Cut-down, Annoyed, Guilt, Eye-opener (CAGE) questionnaire scores and problems due to drinking at ages 27 and 42 years. DESIGN: In the Finnish Jyväskylä Longitudinal Study of Personality and Social Development, data have been collected by interviews, inventories and questionnaires. Behavioural data were gathered at ages 8 and 14; data on alcohol consumption were gathered at ages 14, 20, 27, 36 and 42. PARTICIPANTS: A total of 184 males and 163 females; 94% of the original sample of the 8-year-olds. FINDINGS: Family adversities, externalizing problem behaviours, low school success, truancy and substance use in adolescence were associated in early middle age with problems due to drinking in both genders, and to binge drinking and CAGE scores in females. The antecedents varied, however, across the indicators of drinking and gender. The frequency of drinking was least predictable by the studied antecedents. Childhood and adolescent antecedents and drinking up to age 20 explained 43% of males' and 31% of females' problem drinking at age 42; 31% and 19%, respectively, at age 27. CONCLUSIONS: The early warning signs of drinking problems should be taken seriously in the preventive work for alcohol abuse. Problem drinking in early middle age is preceded by maladjustment to school, early age of onset of drinking and heavy drinking in adolescence even more significantly than problem drinking in early adulthood.